Analysis Of Technological, Technological, Pedagogical, And Content Knowledge (TPACK) of Islamic Religious Education Teachers of MTS On Hadas And Najis Materials - Hanafi Hanafi (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
This study aims to analyze the Technological Pedagogical Content Knowledge (TPACK) skills of MTs Islamic Religious Education (PAI) Teachers on Hadas and Najis Material. The method used in this research is descriptive research. In descriptive analysis, researchers do not treat the object of study. The sampling technique used was purposive sampling with 6 Madrasah Tsanawiyah Schools (MTs) in West Lombok Regency, NTB. Data is collected via the TPACK filling tool. Data analysis by coding is based on seven categories in the TPACK framework (CK, PK, TK, PCK, TPK, TCK, TPACK). Based on the results of data analysis, the ability of Madrasah Tsanawiyah (MTs) teachers in West Lombok Regency, West Nusa Tenggara, on hadas and najis material shows (a) there is no difference between groups A and B in the level of TPACK ability. There is a difference in the length of a teacher's teaching experience. The planning and implementation capabilities of TPACK MTs teachers are limited to focus and its tools along with whiteboards and markers, which are implemented in the process of teaching and learning activities using the presentation method in a class by each group of students.